VTT-006, an anti-mitotic compound, binds to the Ndc80 complex and suppresses cancer cell growth in vitro. - Laine Leena J; Mäki-Jouppila Jenni HE; Kutvonen Emma; Tiikkainen Pekka; Nyholm Thomas KM; Tien Jerry F; Umbreit Neil T; Härmä Ville; Kallio Lila; Davis Trisha N; Asbury Charles L; Poso Antti; et al. (Trend MD, 2025)
Hec1 (Highly expressed in cancer 1) resides in the outer kinetochore where it works to facilitate proper kinetochore-microtubule interactions during mitosis. Hec1 is overexpressed in various cancers and its expression shows correlation with high tumour grade and poor patient prognosis. Chemical perturbation of Hec1 is anticipated to impair kinetochore-microtubule binding, activate the spindle assembly checkpoint (spindle checkpoint) and thereby suppress cell proliferation. In this study, we performed high-throughput screen to identify novel small molecules that target the Hec1 calponin homology domain (CHD), which is needed for normal microtubule attachments. 4 million compounds were first virtually fitted against the CHD, and the best hit molecules were evaluated in vitro. These approaches led to the identification of VTT-006, a 1,2-disubstituted-tetrahydro-beta-carboline derivative, which showed binding to recombinant Ndc80 complex and modulated Hec1 association with microtubules in vitro. VTT-006 treatment resulted in chromosome congression defects, reduced chromosome oscillations and induced loss of inter-kinetochore tension. Cells remained arrested in mitosis with an active spindle checkpoint for several hours before undergoing cell death. VTT-006 suppressed the growth of several cancer cell lines and enhanced the sensitivity of HeLa cells to Taxol. Our findings propose that VTT-006 is a potential anti-mitotic compound that disrupts M phase, impairs kinetochore-microtubule interactions, and activates the spindle checkpoint.